GE_GERICHTE C/27101/2012 vom 17. April 2013 - GE Cour de justice (2013)
PROTECTION DE L'UNION CONJUGALE; OBLIGATION D'ENTRETIEN; DÉBUT; TRAIN DE VIE; MAJORITÉ(ÂGE) | CC.163; CC.176.1; CC.176.3; CC.277.2; CC.285.1